Early versus Standard Weight Bearing Following Operative Treatment of Tibial Plateau Fractures: Do We Really Have to Wait So Long? - Heiman, Erick; Menken, Luke G.; Tang, Alex; Vialonga, Mason; Jankowski, Jaclyn M.; Liporace, Frank A.; Yoon, Richard S. (The Journal of Knee Surgery, 2023)
Postoperative management of tibial plateau fractures classically involves a prolonged period between 10 and 12 weeks of nonweight bearing or partial weight bearing. In recent years, there has been some support for earlier weight-bearing protocols although this remains controversial. The goal of this study was to investigate the difference in outcomes between early weight-bearing (EWB) and traditional weight-bearing (TWB) protocols. This investigation is a retrospective review of 92 patients treated with open reduction and internal fixation of tibial plateau fractures at a single institution, from August 2018 to September 2020. Subjects were divided into EWB (< 10 weeks) and traditional nonweight bearing groups (≥ 10 weeks). Key outcome measures collected include injury classification, mechanism of injury, surgical fixation method, bone grafting, time to full weight bearing, radiographic time to union, range-of-motion, all-cause complications, and subsidence at an average follow-up time of 1 year. The EWB group had an earlier average time to weight bearing versus the TWB group (6.5 ± 1.4 vs. 11.8 ± 2.3 weeks, p < 0.0001). There was no difference in the classification of fractures treated between the two groups, with Arbeitsgemeinschaft für Osteosynthesefragen/Orthopaedic Trauma Association B3 fractures the most common in the EWB group, and C3 fractures the most common in the TWB group. Radiographic time to union was no different between the two groups (93.5 ± 53.7 days for EWB vs. 103.7 ± 77.6 days for TWB, p = 0.49). There was no significant difference in complication rates or subsidence. Following operative treatment of tibial plateau fractures, patients who underwent a weight-bearing protocol earlier than 10 weeks were able to recover faster with similar outcomes and complications compared with patients who started weight bearing after 10 weeks or more.Level of Evidence III.
Keywords: tibial plateau fracture; weight bearing as tolerated; early; bony union; complications